Introduction to the proceedings of the RODOSZ/4 Doctoral Conference in Romance Studies - Horváth, Márton Gergely (Verbum – Analecta Neolatina, 2018)
The Doctoral Conference in Romance Studies “RODOSZ” (initially Romanisztikai Doktorandusz Konferencia, now called Romanista Doktoranduszok Konferenciája) was organised for the first time in 2009 by the doctoral schools of Eötvös Loránd University and Pázmány Péter Catholic University. Nine years have passed since two PhD students, Eszter Koós and I, proposed to set up the event, and the formerly nationwide conference that gathered together doctoral students from various fields of Romance studies has now become international. This fourth edition of the conference, organised by the ACRIL (Artes, Critica, Linguistica) research group of the Institute of Romance Studies of Pázmány Péter Catholic University, permitted twenty PhD students from eight different European countries to present their scientific work and to get an insight to a variety of research fields.